Cost-effectiveness of screening for primary aldosteronism in hypertensive patients in Australia: A Markov modelling analysis - Woode, M.E.; Wong, K.; Reid, Christopher; Stowasser, M.; Russell, G.; Gwini, S.; Young, M.J.; Fuller, P.J.; Yang, J.; Chen, G. (2023)
Background:Primary aldosteronism affects 3-14% of hypertensive patients in the primary care setting and up to 30% in the hypertensive referral units. Although primary aldosteronism screening is recommended in patients with treatment-resistant hypertension, diagnosis at an earlier stage of disease may prevent end-organ damage and optimize patient outcomes.Methods:A Markov model was used to estimate the cost-effectiveness of screening for primary aldosteronism in treatment and disease (cardiovascular disease and stroke) naive hypertensive patients. Within the model, a 40-year-old patient with hypertension went through either the screened or the unscreened arm of the model. They were followed until age 80 or death. In the screening arm, the patient underwent standard diagnostic testing for primary aldosteronism if the screening test, aldosterone-to-renin ratio, was elevated above 70 pmol/l: mU/l. Diagnostic accuracies, transition probabilities and costs were derived from published literature and expert advice. The main outcome of interest was the incremental cost effectiveness ratio (ICER).Results:Screening hypertensive patients for primary aldosteronism compared with not screening attained an ICER of AU$35 950.44 per quality-adjusted life year (QALY) gained. The results were robust to different sensitivity analyses. Probabilistic sensitivity analysis demonstrated that in 73% of the cases, it was cost-effective to screen at the commonly adopted willingness-to-pay (WTP) threshold of AU$50 000.Conclusion:The results from this study demonstrated that screening all hypertensive patients for primary aldosteronism from age 40 is cost-effective. The findings argue in favour of screening for primary aldosteronism before the development of severe hypertension in the Australian healthcare setting.